POTENSI PENGEMBANGAN BAHAN AJAR: HANDOUT PADA PEMBELAJARAN IPA SMP BERBASIS PENELITIAN PENGARUH KONSENTRASI NUTRISI AB MIX PADA PERTUMBUHAN TANAMAN BAYAM (Amaranthus tricolor L.) DENGAN TEKNIK HIDROPONIK SISTEM WICK - Rayshatico Perdana Putra; Sri Wulandari; Yuslim Fauziah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study was conducted to determine the effect of nutrient concentrations on plant growth AB Mix the spinach with hydroponic techniques wick system as well as the design for the development of learning handout on SMP IPA in March-May 2016. The study was carried out by two phases: an experiment: the effect of nutrient concentrations AB Mix the spinach plant growth (Amaranthus tricolor L.) with hydroponic techniques and the wick system design stage handout science teaching junior high school. The study used an experimental method performed in Greenhouse Natural Laboratory Biology Education Studies Program FKIP Riau University Pekanbaru. Sampling was done by completely randomized design (CRD) consisting of 4 treatments and 3 replications. The parameters in this study were plant height, leaf number, fresh weight and dry weight of plants. Based on the results of analysis of variance (Anova) at 5% level, giving AB Mix nutrient concentrations showed significantly affect plant growth amaranth (Amaranthus tricolor L.). Mix AB Award nutrient solution with a concentration of 1400 ppm produced growth of crop plants spinach (Amaranthus tricolor L.) is best reached 34.7 cm height, number of leaves strands 9.33, 11.88 g wet weight and dry weight of 0.99 g , Based on the analysis of the potential of the research results can be used as a handout designed development on biotechnology concept for junior high school students.